2022
DOI: 10.17275/per.22.124.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Technical Support on Technology Acceptance Model to Examine the Project PAIR E-Learning System in Distance Learning Modality

Abstract: Adopting technology in this new normal education improved students' engagement and motivation to learn. This paper aimed to investigate the impact of technical support on Technology Acceptance Model to examine Project PAIR in the distance learning modality employing Partial Least Squares-Structural Equation Modeling. Applying a convenience sampling technique, the investigation involved 305 senior high school learners from a secondary school in Cagayan, Philippines. Sample sizes were calculated using the invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Cronbach's alpha and confirmatory analyses are two statistical methods frequently used to evaluate the validity and reliability of such measures (K. Caratiquit, 2022a;K. D. Caratiquit & Caratiquit, 2023;L. J. Caratiquit & Caratiquit, 2022).…”
Section: Reliability and Validity Of The Research Instrumentmentioning
confidence: 99%
“…Cronbach's alpha and confirmatory analyses are two statistical methods frequently used to evaluate the validity and reliability of such measures (K. Caratiquit, 2022a;K. D. Caratiquit & Caratiquit, 2023;L. J. Caratiquit & Caratiquit, 2022).…”
Section: Reliability and Validity Of The Research Instrumentmentioning
confidence: 99%
“…Nevertheless, perceived usefulness had a substantially greater relationship with user behavior when compared with ease of use. Recently, TAM has been successfully employed in prior studies to investigate user acceptance of technology in different contexts (Caratiquit & Caratiquit, 2022;Girish et al, 2022;Sun, 2022). For example, Sun (2022) revealed that perceived usefulness turned to be a significant predictor of instructors' actual usage of online instruction during the Covid-19 pandemic.…”
Section: Theoretical Facetmentioning
confidence: 99%